The benefits and challenges of suitainable practices : A case study at oil and gas companies in Libya - Elabbar, Salem Mohamed B (2024)
This study delves into the complexities of sustainability within the Libyan oil and gas industry. Through in-depth interviews with key personnel from seven prominent companies, the research investigates the practical implementation of sustainable practices. The focus is on understanding the multifaceted impacts – environmental, social, and economic – that these initiatives engender. Findings underscore the industry's commitment to sustainability while simultaneously revealing the formidable challenges hindering progress. Technological limitations, stringent regulatory frameworks, and the need for skilled personnel emerge as critical obstacles. However, the research also demonstrates the potential for significant rewards, including improved financial performance, technological advancements, and enhanced corporate image. By providing a nuanced understanding of the Libyan oil and gas sector's sustainability journey, this study offers valuable insights for industry stakeholders, policymakers, and researchers. It emphasizes the importance of strategic planning, continuous learning, and collaborative efforts to overcome challenges and unlock the full potential of sustainable operations.